An Advanced Nitrogen‐Doped Graphene/Cobalt‐Embedded Porous Carbon Polyhedron Hybrid for Efficient Catalysis of Oxygen Reduction and Water Splitting. (22nd December 2014) - Hou, Yang; Wen, Zhenhai; Cui, Shumao; Ci, Suqin; Mao, Shun; Chen, Junhong
Abstract : A novel hybrid electrocatalyst consisting of nitrogen‐doped graphene/cobalt‐embedded porous carbon polyhedron (N/Co‐doped PCP//NRGO) is prepared through simple pyrolysis of graphene oxide‐supported cobalt‐based zeolitic imidazolate‐frameworks. Remarkable features of the porous carbon structure, N/Co‐doping effect, introduction of NRGO, and good contact between N/Co‐doped PCP and NRGO result in a high catalytic efficiency. The hybrid shows excellent electrocatalytic activities and kinetics for oxygen reduction reaction in basic media, which compares favorably with those of the Pt/C catalyst, together with superior durability, a four‐electron pathway, and excellent methanol tolerance. The hybrid also exhibits superior performance for hydrogen evolution reaction, offering a low onset overpotential of 58 mV and a stable current density of 10 mA cm −2 at 229 mV in acid media, as well as good catalytic performance for oxygen evolution reaction (a small overpotential of 1.66 V for 10 mA cm −2 current density). The dual‐active‐site mechanism originating from synergic effects between N/Co‐doped PCP and NRGO is responsible for the excellent performance of the hybrid. This development offers an attractive catalyst material for large‐scale fuel cells and water splitting technologies. Abstract : A novel hybrid electrocatalyst consisting of nitrogen‐doped graphene/cobalt‐embedded porous carbon polyhedron (N/Co‐doped PCP//NRGO) is obtained through a simple pyrolysis of graphene oxide‐supported cobalt‐based zeolitic imidazolate‐frameworks. The hybrid exhibits excellent electrocatalytic activities for oxygen reduction, hydrogen evolution, and oxygen evolution reactions with good stability. The enhanced performance is correlated with the dual‐active‐site mechanism originating from synergic effects between N/Co‐doped PCP and NRGO sheets.